MICRONUCLEI IN MUCOCYTES AND HELICOBACTER PYLORI INFECTION IN COVE-PATCHING EPITHELIUM OF THE STOMACH IN POPULATION OF RADIOACTIVE CONTAMINATED AREAS - S. N. Lopatin; V. Yu. Kravtsov; S. V. Dudarenko; A. V. Rozhko (Радиационная гигиена)
The investigation of frequencies of micronuclei in mucocytes cover-patching epithelium of the gastric mucosa (GM) in the group of persons living in the contaminated territories (RZT) and in the group of persons who had not a history of radiation exposure, living in Saint-Petersburg. All respondents were patients with chronic gastritis (ICD-10K29.3). Micronucleus test was carried out retrospectively in histological sections obtained from antral gastrobioptatov. Along with the micronucleus test in gastrobioptatah examined patients were conducted immunohistochemical determination of H. pylori. There were significant differences between the residents of contaminated areas and those who have not had a history of radiation exposure in terms of "frequency of mukotsitov gastric mucosa with micronuclei." Maximum frequency of mucocytes with micronuclei was observed in individuals living in radiation-contaminated areas gastric mucosa which was infected with Helicobacter pylori. In the group from radiation-contaminated areas with HPassociated gastritis incidence mucocytes with micronuclei in the gastric mucosa was five times higher than that of patients whose mucosa was not infected HP (p <0.01). Thus, we can assume that the Helicobacter pylori potentiates the mutagenic effects of radiation factor.